(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
An efficient regeneration protocol was established for two varieties (BARI tomato-9 and BARI tomato-15) of tomato (Lycopersicon esculentum Mill.) using three explants namely cotyledonary node, cotyledonary leaf and hypocotyls. Among the three explants, maximum number of shoots was produced from cotyledonary leaf explants of BARI tomato-15 on MS with 2.0 mg/l BAP and 0.5 mg/l IAA. In this combination of BAP and IAA 86%, on an average, cotyledonary leaf explants showed regeneration response 14.12 shoots/explants. Explants from hypocotyl showed best results in MS medium with 2.0 mg/l BAP and 0.2 mg/l IAA in both the varieties. In case of cotyledonary node, BARI tomato-15 showed 6.0 shoot/explant on MS with 2.0 mg/l BAP and 1.0 mg/l IAA. Molecular characterization of total ten varieties of tomato in Bangladesh was done by using six arbitrary oligonucleotide RAPD primers. A total of 140 bands were produced where the highest genetic distance (0.6769) was found between BARI tomato-3 and Mintoo tomato and lowest distance (0.1035) was observed between BARI tomato-7 and BARI tomato-8. This result will be useful for designing future breeding programs. Bangladesh J. Sci. Ind. Res.54(2), 117-124, 2019